Creatine kinase binds more firmly to the M-band of rabbit skeletal muscle myofibrils in the presence of its substrates - Žurmanová, Jitka; Difato, Francesco; Horníková, Daniela; Mejsnar, Jiří; Štefl, Bohumír; Zahradník, Ivan (Molecular and cellular biochemistry, 2007)
Creatine kinase (CK) (E.C. 2.7.3.2) buffers cellular ATP concentration during fluctuating ATP turnover. Muscle cytosolic CK isoform interacts with various subcellular structures where it is functionally coupled with relevant ATPases. However, how this interaction affects its activity is not known. We have therefore studied the interaction of CK with myofibrils and the role of different conformational states of CK molecule induced by ATP, phosphocreatine, ADP and the ATP-creatine pair. Purified rabbit psoas myofibrils with CK specific activity of 0.4+/-0.02 IU/mg were used. The exchange rates between the myofibrillar M-band and its surroundings were measured with fluorofore conjugated CK (IAF) by the Fluorescence Lost in Photobleaching (FLIP) method within a very narrow pH range 7.1-7.15. For CK-IAF without docked substrates, the time derivative of the initial loss of the fluorescent signal within the M-band equalled -3.26 at the fifth second and the decrease reached 82% by the 67th second. For CK-IAF with added substrates, the derivatives fell into the range of -0.95 to -1.30, with respective decreases from 16 to 46% at the 67th second. The results show that the substrates slowed down the exchange rate. This indicates that the strength of the bond between CK and the M-band of myofibrils increased.
Keywords: Animals; Photobleaching; biologické modely; Fluorescent Dyes; Muscle, Skeletal; financování organizované; zvířata; fotovybělování; Rabbits; Protein Binding; kosterní svalová vlákna; Financing, Organized; Creatine Kinase, MM Form; adenosintrifosfát; Male; králíci; Muscle Fibers, Skeletal; kreatinkinasa, forma MM; Adenosine Triphosphate; Models, Biological; fluorescenční barviva; Muscle Proteins; vazba proteinů; mužské pohlaví; svalové proteiny; kosterní svaly